Monoclonal antibodies: their place in applied medicine and their role in the newest infectious disease – history, present, and future. Literature review - Petar Yordanov Atanasov; Maria Georgieva Moneva-Sakelarieva; Yozlem Ali Kobakova; Stefka Achkova Ivanova; Maria Vakrilova Becheva; Angelina Georgieva Kirkova-Bogdanova; Maria Sevdelinova Chaneva; Ventseslava Petrova Atanasova; Radoslav Fedeev Todorov; Nikolay Zarkov Bashev; Ismail Elhanov Bashov; Adel Habib Ibrahim (Pharmacia)
Monoclonal antibodies (mAbs) are immunoglobulins with practically absolute specificity (monospecificity) for a particular antigen (epitope). Over the past three decades, monoclonal antibodies have undergone a remarkable transformation, evolving from their use predominantly as research tools to becoming increasingly powerful therapeutic agents in medical practice. Personalized therapy and targeted treatment of diseases form the cornerstone of modern medicine’s revolutionary capabilities. Monoclonal antibodies are a shining example of personalized therapy, developed based on deep and continuously growing knowledge in the fields of immunology, molecular biology, and biochemistry. The accepted nomenclature for monoclonal antibody names indicates their origin: murine (-omab), chimeric (-ximab), humanized (-zumab), or recombinant (-umab). Monoclonal antibodies belong to the IgG class. Monoclonal antibodies of this class possess specific properties and advantages. They are characterized by optimal pharmacokinetics, stability, and low immunogenicity (especially recombinant forms), a low toxicity profile, and the capacity for large-scale production of specific monoclonal antibodies targeting diverse antigens. The mechanisms of action of monoclonal antibodies include direct cell toxicity, immune-mediated cell destruction, vascular destruction, and immunomodulatory functions. The pathophysiology of many conditions treated with monoclonal antibodies is equally intricate, involving numerous cells and molecules. Monoclonal antibodies, in general, are characterized by good tolerance. The scientific community continues its efforts to enhance their efficacy, reduce their immunogenicity, and optimize their pharmacokinetic properties, as well as attempts to achieve oral (mucosal) bioavailability. The use of monoclonal antibodies in modern medicine is continuously expanding, with their incorporation into therapeutic regimens for numerous severe non-malignant diseases such as asthma, atopic dermatitis, migraine, hypercholesterolemia, osteoporosis, bacterial infections (e.g., anthrax), and viral infections (such as COVID-19). Efforts are being directed not only at improving the structural and functional properties of existing monoclonal antibodies but also at creating new types of antibodies with smaller molecular weights and higher specificity. As a next generation of nanobiotechnology, natural and synthetic nanobodies have been utilized in numerous fields of biomedicine, including as biomolecular materials, for various biological studies, and in medical diagnostics and immunotherapy. Monoclonal antibodies and antibody-based molecules offer a reliable opportunity to effectively counter emerging viral pathogens and antibiotic-resistant bacteria. When administered to patients with a healthy immune system, they can provide necessary prophylaxis against specific diseases, acting as vaccine-like molecules and promoting long-term, antimicrobial-specific immune responses. Monoclonal antibodies have been identified as a potentially effective therapy for preventing the progression of COVID-19 in patients at high risk of developing severe disease.